(untitled) - Radcliffe, Doug (San Francisco, 2003)
Flight Simulator 2004: A Century of Flight lets pilots of all ages and abilities experience history in the cockpit of such famous planes as the Wright Flyer, the Spirit of St. Louis, and the Douglas DC-3. This official strategy guide, written with the full cooperation of Microsoft Game Studios, will help you deepen your knowledge and enjoyment of every aspect of flight, whether you're trying to land that Comet in a crosswind or request take-off clearance from ATC so you can get that 737 full of passengers to Chicago on time.
Keywords: Airplanes,Máy bay; Computer simulation,Sự mô phỏng máy tính